Kahoot aplicada en la evaluación sumativa en un curso de matemática discreta - Valles-Pereira, Ricardo Enrique; Mota-Villegas, Dorenis Josefina (Revista Científica, 2020)
This article describes a classroom experience, the result of research, in which a group of students of the Discrete Mathematics course was evaluated on a fundamental topic such as set theory and its operations through Venn diagrams. This, by means of the incorporation of a playful technological tool called Kahoot, which allows to create presentations / interactive games in which a diverse number of people can participate at the same time, from two people to a large number, through electronic devices. The objective was to awaken in the student interest in mastering mathematical subjects and in speeding up the speed of mental thinking through the competitive stimulus of comparing their knowledge with their peers. As a methodology, a field study was carried out based on the bibliographic review of the theoretical elements of interest, in which students who study the subject of Discrete Mathematics related to Systems and Computing Engineering careers were used as a sample, in the period 2018 -2019, in a particular Latin American university. The preliminary results showed a total acceptance of Kahoot as an evaluative tool and a good percentage of correct answers related to the subject evaluated with that tool.